2016
DOI: 10.1155/2016/8232830
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Human Basophil Biology from Neglect towards Understanding of Their Immune Functions

Abstract: Being discovered long ago basophils have been neglected for more than a century. During the past decade evidence emerged that basophils share features of innate and adaptive immunity. Nowadays, basophils are best known for their striking effector role in the allergic reaction. They hence have been used for establishing new diagnostic tests and therapeutic approaches and for characterizing natural and recombinant allergens as well as hypoallergens, which display lower or diminished IgE-binding activity. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 186 publications
0
19
0
2
Order By: Relevance
“…This was confirmed when mice were injected with cultured mast cells which resulted in tick rejection following infestation of Haemophysalis longicornis ticks, with no tick rejection in mast cell deficient mice (Matsuda et al, 1987 ). A recent review of basophil functions confirms their effector role in allergic reactions, however basophils also share features of innate and adaptive immunity (Steiner et al, 2016 ) which again associates well with the tick resistant bovine phenotype. Steiner et al ( 2016 ) examined the ever expanding function of basophils including the modulation of several cytokines, Toll-like receptors and chemokines (including CXCL10, CCR1, CCR7 described as up-regulated in certain tick resistant cattle studies, Table 1 ).…”
Section: Cellular Physiology Associated With Host Resistancementioning
confidence: 91%
“…This was confirmed when mice were injected with cultured mast cells which resulted in tick rejection following infestation of Haemophysalis longicornis ticks, with no tick rejection in mast cell deficient mice (Matsuda et al, 1987 ). A recent review of basophil functions confirms their effector role in allergic reactions, however basophils also share features of innate and adaptive immunity (Steiner et al, 2016 ) which again associates well with the tick resistant bovine phenotype. Steiner et al ( 2016 ) examined the ever expanding function of basophils including the modulation of several cytokines, Toll-like receptors and chemokines (including CXCL10, CCR1, CCR7 described as up-regulated in certain tick resistant cattle studies, Table 1 ).…”
Section: Cellular Physiology Associated With Host Resistancementioning
confidence: 91%
“…In mice, TSLP‐elicited basophils preferentially produce IL‐4 . Whether this distinction in TSLP‐elicited and IL‐3‐elicited basophils exists in humans is uncertain …”
Section: Pruritogens Associated With Basophilsmentioning
confidence: 99%
“…Recent studies have revealed that mast cells and basophils control the innate immune response in various ways. IgE-induced immune response and degranulation from mast cells and basophils are considered to be host defense responses against parasites [15,16,18,19,21,55]. In this study, we found that H 2 O 2 produced by mitis group streptococci inhibits the IgEinduced degranulation from RBL-2H3 cells.…”
Section: Discussionmentioning
confidence: 58%
“…Activated mast cells and basophils are reported to produce IL-4 [15,16,18,21]. Thus, IL-4 in the culture medium of the treated cells was also measured (Fig 7).…”
Section: Il-4 Release From Rbl-2h3 Cellsmentioning
confidence: 96%
See 1 more Smart Citation